Characterization of B-Genome Specific High Copy hAT MITE Families in Brassica nigra Genome - Perumal, Sampath; James, Brian; Tang, Lily; Kagale, Sateesh; Robinson, Stephen J.; Yang, Tae-Jin; Parkin, Isobel A. P. (Frontiers in Plant Science, 2020)
Miniature inverted-repeat transposable elements (MITEs) are non-autonomous class II transposons which have been shown to influence genome evolution. Brassica nigra L. (B-genome) is one of three Brassica diploids cultivated primarily as an oil crop, which harbours novel alleles important for breeding. Two new high copy hAT MITE families (BniHAT-1 and BniHAT-2) from the B-genome were characterized and their prevalence assessed in the genomes of the related diploids, Brassica rapa L. (A) and Brassica oleracea L. (C). Both novel MITE families were present at high copy numbers in the B-genome with 434 and 331 copies of BniHAT-1 and BniHAT-2, respectively. Yet less than 20 elements were identified in the genome assemblies of the A, and C -genomes, supporting B-genome specific proliferation of these MITE families. Although apparently randomly distributed across the genome, 68% and 70% of the B-genome MITEs were present within 2 kb flanking regions of annotated genes suggesting they might influence gene expression and/or function. In addition, MITE derived microRNAs and transcription factor binding sites suggested a putative role in gene regulation. Age of insertion analysis revealed that the major proliferation of these elements occurred during 2-3 million years ago. Additionally, site-specific polymorphism analyses showed that 44% MITEs were undergoing active amplification into the B-genome. Overall, this study provides a comprehensive analyses of two high copy MITE families, which were specifically amplified in the B-genome, suggesting a potential role in shaping the Brassica B-genome.